Composite diaphragm for alkaline water electrolysis as well as preparation method and application of composite diaphragm

By adopting a composite separator structure of polymer porous layer and composite porous coating in alkaline water electrolytic separator, combined with pre-evaporation and phase conversion technology, the problem of powder loss in existing separators in strong alkaline medium is solved, and the performance of high chemical and mechanical stability, low gas permeability and low surface resistance is achieved, meeting the needs of industrial production.

CN119615276AActive Publication Date: 2025-03-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411831806.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-14
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing alkaline water electrolytic separators have powder loss problems in strong alkaline media, resulting in insufficient chemical and mechanical stability, poor hydrophilic performance, high gas permeability and surface resistance, which cannot meet the needs of industrial production.

Method used

The composite separator structure is adopted, including a polymer porous layer and a composite porous coating. The polymer porous layer is composed of polysulfone and chitosan. The composite porous coating is composed of alkali-resistant polymer polymers and inorganic nanoparticles. Pre-evaporation and phase conversion technology are used during the preparation process to form a dense cortex and three-dimensional porous layer.

Benefits of technology

It significantly improves the chemical and mechanical stability of the composite separator in strong alkali medium, enhances the wettability of alkali liquid, reduces gas permeability and surface resistance, suppresses powder loss, and meets the needs of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615276A_ABST
    Figure CN119615276A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm for alkaline water electrolysis as well as a preparation method and application of the composite diaphragm. The composite diaphragm sequentially comprises a polymer porous layer and a composite porous coating, wherein the composite porous coating contains a support body with a latticed structure; the polymer porous layer is composed of polysulfone and chitosan; the composite porous coating is composed of an alkali-resistant high-molecular polymer and inorganic nanoparticles. The composite diaphragm provided by the invention has high chemical and mechanical stability, high porosity and small aperture in a strong alkali medium, has good wettability to alkali liquor, low gas permeability and low surface resistance, and can restrain the problem of powder falling of the modified PPS diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alkaline water electrolysis, and more specifically, to a composite diaphragm for alkaline water electrolysis and a preparation method and application thereof. Background Art

[0002] As a renewable energy source, hydrogen energy has the characteristics of high combustion heat, no pollution and wide sources, and is regarded as one of the ideal energy carriers.

[0003] Alkaline water electrolysis is a mature green hydrogen production technology. The alkaline water electrolysis device includes an electrolyzer, electrodes and a diaphragm. When powered on, hydrogen is produced on the cathode side and oxygen is produced on the anode side. In the traditional alkaline aqueous solution electrolysis process, asbestos cloth or polyphenylene sulfide (PPS) cloth is usually used as a diaphragm to isolate the electrodes and conduct the hydroxide (OH) in the electrolyte. - ) is connected to the internal circuit. Since the pore size of asbestos cloth or polyphenylene sulfide (PPS) is large, in order to avoid the potential safety hazards caused by the mixing of the generated hydrogen and oxygen; at the same time, the hydrophilicity of asbestos cloth and polyphenylene sulfide cloth is poor, and the resistance in the tank is large, the system consumes a lot of energy, resulting in excessively high electrolysis costs.

[0004] Improving the diaphragm is one of the main methods to optimize the technology of hydrogen production by water electrolysis. For example, the Chinese patent with publication number CN115029732A discloses a diaphragm for alkaline water electrolysis, which is made of organic polymer resin, porogen, inorganic nanoparticles and a support. The diaphragm has good wettability, but the interaction between the polymer and the inorganic nanoparticles is low, and there will be a serious powder loss problem during use, resulting in the diaphragm being unable to meet the performance requirements of hydrogen production by water electrolysis.

[0005] Therefore, how to solve the powdering problem of modified PPS diaphragms and develop diaphragm materials with high chemical and mechanical stability in strong alkaline media, good wettability to alkali solutions, low gas permeability, low surface resistance, simple process, low cost, and suitability for industrial production to meet the needs of hydrogen production by water electrolysis is an urgent problem to be solved in this field. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a composite diaphragm for alkaline water electrolysis which has high chemical and mechanical stability in a strong alkaline medium, good wettability to alkaline solution, low gas permeability and low surface resistance, and can inhibit the powdering problem of the modified PPS diaphragm, as well as a preparation method and application thereof.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A composite diaphragm for alkaline water electrolysis, the composite diaphragm comprises: a polymer porous layer and a composite porous coating in sequence; wherein the composite porous coating contains a support body with a grid structure; the polymer porous layer is composed of polysulfone and chitosan; the composite porous coating is composed of an alkali-resistant polymer and inorganic nanoparticles.

[0009] Optionally, the alkali-resistant high molecular polymer is polysulfone.

[0010] Optionally, the inorganic nanoparticles include at least one of zirconium oxide, titanium dioxide and cerium oxide, and have a particle size of 50-200 nm.

[0011] Optionally, the support is a polyphenylene sulfide mesh; the support has a thickness of 100-300 μm, and a mesh size of 20-200 meshes, preferably 100-150 meshes.

[0012] Optionally, the composite membrane has a thickness of 200-500 μm.

[0013] Optionally, the thickness of the polymer porous layer is 5-50 μm.

[0014] Optionally, the composite porous coating has a thickness of 150-495 μm.

[0015] Optionally, the average pore size of the polymer porous layer is 2-10 μm.

[0016] Optionally, the average pore size of the composite porous coating is 60-150 nm.

[0017] Optionally, the surface resistance of the composite diaphragm is ≤0.30Ω / cm 2 , bubble point pressure ≥3bar.

[0018] Optionally, the contact angle between the composite membrane and 30% KOH alkali solution is ≤8°.

[0019] Optionally, the porosity of the composite membrane is ≥63%.

[0020] The present invention also discloses a method for preparing the composite diaphragm for alkaline water electrolysis as described above, comprising the following steps:

[0021] S1, mixing inorganic nanoparticles, alkali-resistant high molecular polymer, pore-forming agent and organic solvent 1 evenly to prepare coating slurry;

[0022] S2, applying the coating slurry on the surface of the support, and solidifying it by non-solvent induced phase conversion to form a composite porous coating to obtain a first diaphragm;

[0023] S3, dissolving polysulfone, chitosan and organic solvent 2 to obtain a spinning solution;

[0024] S4, electrospinning the spinning solution onto the surface of the first diaphragm to form a polymer porous layer, followed by heat pressing to obtain the composite diaphragm for alkaline water electrolysis.

[0025] Optionally, in step S1, the coating slurry is prepared by adding 10-20wt% of polysulfone and 1-5wt% of a pore-forming agent to 35-65wt% of an organic solvent 1, stirring at 300-2000r / min at room temperature for 1-5h to obtain a polymer solution; adding 24-40wt% of zirconium oxide, stirring at 300-2000r / min at room temperature for 1-5h, then stirring at a stirring speed of 50-100r / min for 1-3h, and standing for degassing for 2-6h to obtain the coating slurry.

[0026] Optionally, in step S1, the pore-forming agent includes at least one of polyvinyl pyrrolidone and polyvinyl alcohol; and the organic solvent 1 includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0027] Optionally, in step S2, the first diaphragm is prepared by:

[0028] Placing a support on a glass plate, and applying the coating slurry on the support using a scraper to obtain a liquid film with a thickness of 300-650 μm;

[0029] The liquid film is placed in a constant temperature and humidity chamber for pre-evaporation to obtain a primary film;

[0030] The primary membrane is placed in a coagulation bath for phase inversion for 1-10 minutes, then soaked and cleaned with deionized water for multiple times until the water is transparent and not turbid, and finally placed in an oven at 45-65° C. for drying to obtain the first diaphragm.

[0031] Optionally, the pre-evaporation conditions are: temperature of 60-95° C., humidity of 35-50%, and pre-treatment time of 15-45 s.

[0032] Optionally, the temperature of the coagulation bath is 5-60°C; the solvent used in the coagulation bath includes a combination of deionized water and a second solvent; wherein the second solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide; based on the total mass of deionized water and the second solvent as 100%, the mass of the second solvent is 15-40%.

[0033] Optionally, the soaking and cleaning is performed 3-5 times, each time lasting 5-20 minutes; and the drying time is 15-30 minutes.

[0034] Optionally, in step S3, the spinning solution is prepared by mixing 5-10wt% of polysulfone, 5-10wt% of chitosan and 80-90wt% of organic solvent 2, and stirring and dissolving them in an oil bath at 50-100°C for 5-10h to obtain the spinning solution.

[0035] Optionally, the organic solvent 2 includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0036] Optionally, the electrospinning in step S4 includes: adding the spinning solution into a syringe, the receiving end being the first diaphragm, and performing electrospinning under the conditions of a voltage of 15-30 kV, an extrusion speed of 1.5-3 ml / h, and a receiving distance of 8-25 cm;

[0037] Optionally, the hot pressing treatment includes: hot pressing for 3-15 min under the conditions of 80-120° C. and 5-15 MPa.

[0038] The present invention also discloses an application of the composite diaphragm for alkaline water electrolysis as described above, or the composite diaphragm for alkaline water electrolysis prepared by the preparation method described above in hydrogen production by alkaline water electrolysis.

[0039] Implementing the embodiments of the present invention will have the following beneficial effects:

[0040] 1. In the composite diaphragm for alkaline water electrolysis provided by the present invention, the support body containing a grid structure can ensure the mechanical strength of the composite diaphragm; the composite porous coating provides the composite diaphragm with good hydrophilicity and low gas permeability; the chitosan in the polymer porous layer is rich in hydroxyl groups, which can improve the affinity with the electrolyte, and the cationicity of chitosan can be neutralized or form micelles with anions, further improving the hydrophilicity of the composite diaphragm and reducing the surface resistance; more importantly, the polymer porous layer can significantly inhibit the problem of powdering of the modified PPS diaphragm for alkaline water electrolysis; finally, the composite diaphragm is endowed with high chemical and mechanical stability, high porosity and small pore size, good wettability to alkali solution, low gas permeability and low surface resistance in a strong alkaline medium.

[0041] 2. The composite membrane for alkaline water electrolysis provided by the present invention adopts a combination of pre-evaporation and phase conversion to finally form a composite porous coating having a dense skin layer and a three-dimensional porous layer. The dense skin layer hinders hydrogen permeation and provides a high bubble point pressure; the three-dimensional porous layer gives it good wettability and low surface resistance, while retaining strong mechanical strength. Finally, the composite membrane is given high mechanical stability, good wettability to alkali solution, low gas permeability and low surface resistance; at the same time, the preparation method is easy to control and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a morphology diagram of the composite diaphragm in Example 1 of the present invention.

[0043] Figure 2 It is a morphology diagram of the composite diaphragm in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0045] Example 1

[0046] A method for preparing a composite diaphragm for alkaline water electrolysis comprises the following steps:

[0047] S1: 20wt% polysulfone and 5wt% polyvinyl pyrrolidone were added to 51wt% N-methyl pyrrolidone, and stirred at 2000r / min for 1h at room temperature to obtain a polymer solution; 24wt% zirconium oxide (particle size 50nm) was added, and the mixture was stirred at 2000r / min for 3h at room temperature, and the stirring speed was reduced to 100r / min, and the mixture was stirred for 3h, and the mixture was allowed to stand for degassing for 3h to obtain a coating slurry; a polyphenylene sulfide mesh (thickness 200μm, specification 150 mesh) was placed on a glass plate, and the above-mentioned slurry was scraped with a scraper. The coating slurry is coated on a support to obtain a liquid film with a thickness of 650 μm including a porous support layer; the liquid film is pre-evaporated for 15 seconds in a constant temperature and humidity chamber at a temperature of 95°C and a humidity of 50% to obtain a primary membrane; the primary membrane is placed in a 60°C coagulation bath for phase transformation for 3 minutes, the solvent used in the coagulation bath is 65% deionized water and 35% N-methylpyrrolidone, and then immersed and cleaned with deionized water for 3 times, each time for 15 minutes, until the water is transparent and not turbid, and finally placed in a 45°C oven for drying for 30 minutes to obtain a first diaphragm.

[0048] S2: 5wt% polysulfone, 10wt% chitosan and 85wt% N,N-dimethylformamide were mixed, and dissolved in an oil bath at 100°C with stirring for 5h to obtain a spinning solution; the spinning solution was added into a syringe, and the receiving end was the first diaphragm; electrospinning was performed under the conditions of a voltage of 18kV, an extrusion speed of 1.5ml / h, and a receiving distance of 12cm, and then hot-pressed at 120°C and 5MPa for 3min to obtain a composite diaphragm for alkaline water electrolysis with a thickness of 500μm.

[0049] Example 2

[0050] A method for preparing a composite diaphragm for alkaline water electrolysis comprises the following steps:

[0051] S1: Add 17wt% polysulfone and 3wt% polyvinyl pyrrolidone to 40wt% N,N-dimethylacetamide, stir at 1000r / min for 3h at room temperature to obtain a polymer solution; add 40wt% zirconium oxide (particle size of 100nm), continue stirring at 1000r / min for 5h at room temperature, reduce the stirring speed to 80r / min, continue stirring for 2h, stand and degas for 2h to obtain a coating slurry; place a polyphenylene sulfide mesh (thickness 300μm, specification 100 mesh) on a glass plate, use a scraper to apply the above coating slurry on the support to obtain a liquid film with a thickness of 650μm including a porous support layer; pre-evaporate the liquid film in a constant temperature and humidity chamber at a temperature of 60℃ and a humidity of 45% for 35s to obtain a primary membrane; place the primary membrane in a 50℃ coagulation bath for phase inversion for 1min, the solvent used in the coagulation bath is 60% deionized water and 40% N,N-dimethylacetamide, and then soak and clean it with deionized water for 4 times, each time for 5 minutes, until the water is transparent and not turbid, and finally place it in a 65°C oven to dry for 20 minutes to obtain the first diaphragm.

[0052] S2: 10wt% polysulfone, 8wt% chitosan and 82wt% N,N-dimethylacetamide were mixed, and dissolved in an oil bath at 80°C with stirring for 7h to obtain a spinning solution; the spinning solution was added into a syringe, and the receiving end was the first diaphragm; electrospinning was performed under the conditions of a voltage of 15kV, an extrusion speed of 2.5ml / h, and a receiving distance of 8cm, and then hot-pressed at 100°C and 15MPa for 5min to obtain a composite diaphragm for alkaline water electrolysis with a thickness of 500μm.

[0053] Example 3

[0054] A method for preparing a composite diaphragm for alkaline water electrolysis comprises the following steps:

[0055] S1: Add 10wt% polysulfone and 1wt% polyvinyl alcohol to 65wt% N,N-dimethylformamide, stir at 300r / min for 5h at room temperature to obtain a polymer solution; add 24wt% zirconium oxide (particle size is 200nm), continue to stir at 300r / min for 1h at room temperature, reduce the stirring speed to 50r / min, continue to stir for 1h, stand and degas for 6h to obtain a coating slurry; place a polyphenylene sulfide mesh (thickness 100μm, specification 120 mesh) on a glass plate, use a scraper to apply the above coating slurry on the support to obtain a liquid film with a thickness of 300μm including a porous support layer; pre-evaporate the liquid film in a constant temperature and humidity chamber at a temperature of 75℃ and a humidity of 35% for 45s to obtain a primary membrane; place the primary membrane in a 5℃ coagulation bath for phase inversion for 10min, the solvent used in the coagulation bath is 85% deionized water and 15% N,N-dimethylformamide, and then soak and wash with deionized water for 5 times, each time for 20 minutes, until the water is transparent and not turbid, and finally place it in a 55°C oven to dry for 15 minutes to obtain the first diaphragm.

[0056] S2: 5wt% polysulfone, 5wt% chitosan and 90wt% N-methylpyrrolidone were mixed and dissolved in a 50℃ oil bath with stirring for 10h to obtain a spinning solution; the spinning solution was added to a syringe, and the receiving end was the first diaphragm. Electrospinning was performed under the conditions of a voltage of 30kV, an extrusion speed of 2ml / h, and a receiving distance of 25cm to obtain a composite diaphragm containing a polymer porous layer, and then hot pressed at 80℃ and 8MPa for 10min to obtain a composite diaphragm for alkaline water electrolysis with a thickness of 200μm.

[0057] Example 4

[0058] A method for preparing a composite diaphragm for alkaline water electrolysis comprises the following steps:

[0059] S1: Add 20wt% polysulfone and 5wt% polyvinyl pyrrolidone to 35wt% N-methyl pyrrolidone, stir at 2000r / min for 1h at room temperature to obtain a polymer solution; add 40wt% zirconium oxide (particle size 50nm), continue stirring at 2000r / min for 3h at room temperature, reduce the stirring speed to 100r / min, continue stirring for 3h, stand and degas for 3h to obtain a coating slurry; place a polyphenylene sulfide mesh (thickness 200μm, specification 150 mesh) on a glass plate, use a scraper to apply the above coating slurry on the support to obtain a liquid film with a thickness of 550μm including a porous support layer; pre-evaporate the liquid film in a constant temperature and humidity chamber at a temperature of 85℃ and a humidity of 40% for 25s to obtain a primary membrane; place the primary membrane in a 60℃ coagulation bath for phase inversion for 3min, the solvent used in the coagulation bath is 75% deionized water / 25% N-methylpyrrolidone, and then soak and clean it with deionized water for 3 times, each time for 15 minutes, until the water is transparent and not turbid, and finally place it in a 45°C oven to dry for 30 minutes to obtain the first diaphragm.

[0060] S2: 10wt% polysulfone, 10wt% chitosan and 80wt% N,N-dimethylformamide were mixed, stirred and dissolved in an oil bath at 100℃ for 5h to obtain a spinning solution; the spinning solution was added to a syringe, and the receiving end was the first diaphragm. Electrospinning was performed under the conditions of voltage of 18kV, extrusion speed of 1.5ml / h, and receiving distance of 12cm to obtain a composite diaphragm containing a polymer porous layer, and then hot pressed at 120℃ and 5MPa for 35min to obtain a composite diaphragm for alkaline water electrolysis with a thickness of 450μm.

[0061] Comparative Example 1

[0062] A method for preparing a composite diaphragm for alkaline water electrolysis comprises the following steps:

[0063] S1: 20wt% polysulfone and 5wt% polyvinyl pyrrolidone were added to 51wt% N-methyl pyrrolidone, and stirred at 2000r / min for 1h at room temperature to obtain a polymer solution; 24wt% zirconium oxide (particle size 50nm) was added, and the mixture was stirred at 2000r / min for 3h at room temperature, and the stirring speed was reduced to 100r / min, and the mixture was stirred for 3h, and the mixture was allowed to stand for degassing for 3h to obtain a coating slurry; a polyphenylene sulfide mesh (thickness 200μm, specification 150 mesh) was placed on a glass plate, and the above-mentioned slurry was scraped with a scraper. The coating slurry is coated on a support to obtain a liquid film with a thickness of 450 μm including a porous support layer; the liquid film is pre-evaporated for 15 seconds in a constant temperature and humidity chamber at a temperature of 95° C. and a humidity of 50% to obtain a primary membrane; the primary membrane is placed in a 60° C. coagulation bath for phase transformation for 3 minutes, the solvent used in the coagulation bath is 65% deionized water and 35% N-methylpyrrolidone, and then immersed and cleaned with deionized water for 3 times, each time for 15 minutes, until the water is transparent and not turbid, and finally placed in a 45° C. oven for drying for 30 minutes to obtain a first diaphragm.

[0064] S2: The first diaphragm obtained in the previous step was hot-pressed at 120° C. and 5 MPa for 3 min to obtain a composite diaphragm for alkaline water electrolysis with a thickness of 480 μm.

[0065] Comparative Example 2

[0066] This comparative example uses a commercial polyphenylene sulfide separator with a thickness of 700 μm.

[0067] Test Case

[0068] Performance test 1: The performance of the diaphragms of Examples 1 to 4 and Comparative Examples 1 to 2 was tested. The specific test method is as follows. The test results are shown in Tables 1 and Figure 1-2 .

[0069] Porosity: The porosity of the composite membrane is measured by weighing. Take a 5cm*5cm membrane and fully wet it with deionized water. Quickly and gently wipe the moisture on the surface of the membrane with filter paper, and accurately weigh the mass of the wet membrane with an electronic analytical balance. Then vacuum dry it at 60℃ for more than 3h, and then accurately weigh the mass of the dry membrane. The membrane porosity formula is as follows:

[0070]

[0071] Where, ε is the porosity (%); ρ is the density of water (g / mL); A is the membrane area (cm 2 ), l is the thickness of the membrane in the wet state (cm), m2 and m1 are the masses of the membrane in the wet and dry states, respectively (g).

[0072] Surface resistance: The surface resistance is measured by electrochemical impedance spectroscopy. A two-electrode system is used. A 20.1mm×20.1mm square window is opened in the middle of two 75mm×75mm×8mm polytetrafluoroethylene plates. Two 20mm×20mm×0.5mm platinum sheets are placed in the window. A diaphragm is placed in the middle of the platinum sheets, and the diaphragm is 3mm away from the platinum sheets. The polytetrafluoroethylene sheets are tightly fixed with polytetrafluoroethylene screws and nuts. Put it in a beaker containing 30% KOH solution, put the beaker in a water bath at a constant temperature of 30°C, and measure the electrochemical impedance using an electrochemical workstation.

[0073] The diaphragm surface resistance is calculated as follows:

[0074] Rs=(R1-R0)×S

[0075] Where: RS: Surface resistance of the diaphragm, Ω·cm 2 ; R0: solution resistance between two electrodes without diaphragm, Ω; R1: resistance between small chambers after adding diaphragm, Ω; S: electrode or diaphragm area, cm 2 .

[0076] Bubble point pressure: The bubble point pressure of the diaphragm is measured by the bubble point method according to GB / T 2679.14-1996. First, the membrane is completely soaked with the test liquid water, and then the gas pressure on the membrane side is increased slowly, and the bubbling of the gas passing through the membrane side is observed. When the gas passes through the liquid seal layer of the membrane and the first series of continuous bubbles appears, the corresponding pressure is the bubble point pressure.

[0077] Average pore size: The average pore size of the membrane is measured by the bubble point method according to GB / T 2679.14-1996. First, the membrane is completely soaked with the test liquid water, and then the gas pressure on the membrane side is increased at a slow rate, and the bubbling of the gas passing through the membrane side is observed, and finally the average pore size of the membrane is output.

[0078] Tensile strength: According to the national standard GB1039-79, the tensile strength of the diaphragm is tested using an electronic universal testing machine. First, the diaphragm is cut into a strip sample with a length of 60 mm and a width of 10 mm. Then, under the conditions of 25±2℃ and relative humidity of 65±5%, a static tensile load is applied to the diaphragm to be tested on a tensile machine to determine the tensile strength of the sample.

[0079] Contact angle: The contact angle of the film was measured using a contact angle meter. During the test, the film sample was placed flat on the sample table, 2 μL of 30 wt% KOH was dropped onto the film surface using a graduated syringe, the baseline position was adjusted, and the data was recorded after 15 seconds. Each sample was tested at least three times.

[0080] Anti-fall-off weight loss ratio (%): Place the diaphragm in an ultrasonic vibrator and vibrate at 180W for 60s, and calculate the diaphragm weight loss ratio.

[0081] Table 1 Test results of Examples 1-4 and Comparative Examples 1-2

[0082]

[0083] Depend on Figure 1 and Figure 2 It can be seen that the composite membrane in Example 1 of the present invention has a multilayer structure, which includes: a polymer porous layer containing polysulfone and chitosan; a composite porous coating layer combined with the polymer porous layer; and a support body containing a grid-like structure contained in the composite porous coating layer. Compared with Example 1, the composite membrane in Comparative Example 1 does not contain a polymer porous layer, and the remaining components and structures are the same.

[0084] As shown in Table 1, compared with Comparative Examples 1-2, the composite membranes described in Examples 1 to 4 have high porosity, low surface resistance, high bubble point pressure and high lyophilicity, while maintaining high mechanical strength at a low thickness. The reason for this is that in the multilayer structure of the composite membrane of the present invention, the support body containing a grid structure provides the mechanical strength of the composite membrane; the composite porous coating provides the composite membrane with good hydrophilicity and low gas permeability; the chitosan in the polymer porous layer is rich in hydroxyl groups, which can improve the affinity with the electrolyte, and the cationicity of the chitosan can neutralize or form micelles with anions, further improving the hydrophilicity of the composite membrane and reducing the surface resistance.

[0085] In addition, by observing Comparative Examples 1-2, it can be found that the anti-shedding ability of the composite diaphragm in the embodiment of the present invention is increased. This is because compared with Comparative Examples 1-2, the polymer porous layer added in the embodiment of the present invention significantly inhibits the powdering problem of the modified PPS diaphragm for alkaline water electrolysis.

[0086] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A composite diaphragm for alkaline water electrolysis, characterized in that: The composite membrane comprises: a polymer porous layer and a composite porous coating layer in sequence; wherein the composite porous coating layer contains a support body with a grid structure; The polymer porous layer is composed of polysulfone and chitosan; The composite porous coating consists of alkali-resistant high molecular polymer and inorganic nanoparticles.

2. The composite diaphragm for alkaline water electrolysis according to claim 1, characterized in that: The alkali-resistant high molecular polymer is polysulfone; The inorganic nanoparticles include at least one of zirconium oxide, titanium dioxide and cerium oxide, and have a particle size of 50-200 nm; The support is a polyphenylene sulfide net; The thickness of the support body is 100-300 μm, and the mesh number is 20-200 meshes.

3. The composite diaphragm for alkaline water electrolysis according to claim 1, characterized in that: The thickness of the composite diaphragm is 200-500 μm; The thickness of the polymer porous layer is 5-50 μm; The thickness of the composite porous coating is 150-495 μm; The average pore size of the polymer porous layer is 2-10 μm; The average pore size of the composite porous coating is 60-150 nm; The surface resistance of the composite diaphragm is ≤0.30Ω / cm 2 , bubble point pressure ≥ 3bar; The contact angle between the composite membrane and 30% KOH alkali solution is ≤8°; The porosity of the composite membrane is ≥63%.

4. A method for preparing a composite diaphragm for alkaline water electrolysis according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing inorganic nanoparticles, alkali-resistant high molecular polymer, pore-forming agent and organic solvent 1 evenly to prepare coating slurry; S2, applying the coating slurry on the surface of the support, and solidifying it by non-solvent induced phase conversion to form a composite porous coating to obtain a first diaphragm; S3, dissolving polysulfone, chitosan and organic solvent 2 to obtain a spinning solution; S4, electrospinning the spinning solution onto the surface of the first diaphragm to form a polymer porous layer, followed by heat pressing to obtain the composite diaphragm for alkaline water electrolysis.

5. The preparation method according to claim 4, characterized in that: In the step S1, the coating slurry is prepared by: adding 10-20wt% of polysulfone and 1-5wt% of pore-forming agent to 35-65wt% of organic solvent 1, stirring at 300-2000r / min at room temperature for 1-5h to obtain a polymer solution; adding 24-40wt% of zirconium oxide, stirring at 300-2000r / min at room temperature for 1-5h, then reducing the stirring speed to 50-100r / min, continuing to stir for 1-3h, and standing for degassing for 2-6h to obtain the coating slurry; The pore-forming agent includes at least one of polyvinyl pyrrolidone and polyvinyl alcohol; the organic solvent 1 includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

6. The preparation method according to claim 4, characterized in that: In step S2, the preparation method of the first diaphragm is: Placing a support on a glass plate, and applying the coating slurry on the support using a scraper to obtain a liquid film with a thickness of 300-650 μm; The liquid film is placed in a constant temperature and humidity chamber for pre-evaporation to obtain a primary film; The primary membrane is placed in a coagulation bath for phase inversion for 1-10 minutes, then soaked and cleaned with deionized water for multiple times until the water is transparent and not turbid, and finally placed in an oven at 45-65° C. for drying to obtain the first diaphragm.

7. The preparation method according to claim 6, characterized in that: The pre-evaporation conditions are: temperature of 60-95°C, humidity of 35-50%, and pre-treatment time of 15-45s; The temperature of the coagulation bath is 5-60°C; The solvent used in the coagulation bath includes a combination of deionized water and a second solvent; wherein the second solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide; based on the total mass of deionized water and the second solvent as 100%, the mass of the second solvent is 15-40%; The soaking and cleaning is performed 3-5 times, each time lasting 5-20 minutes; The drying time is 15-30 minutes.

8. The preparation method according to claim 4, characterized in that: In the step S3, the spinning solution is prepared by mixing 5-10 wt% of polysulfone, 5-10 wt% of chitosan and 80-90 wt% of organic solvent 2, and stirring and dissolving them in an oil bath at 50-100° C. for 5-10 hours to obtain the spinning solution; The organic solvent 2 includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.

9. The preparation method according to claim 4, characterized in that: The electrospinning in step S4 includes: adding the spinning solution into a syringe, the receiving end is a first diaphragm, and performing electrospinning under the conditions of a voltage of 15-30 kV, an extrusion speed of 1.5-3 ml / h, and a receiving distance of 8-25 cm; The hot pressing treatment comprises: hot pressing for 3-15 minutes under the conditions of 80-120° C. and 5-15 MPa.

10. Use of the composite diaphragm for alkaline water electrolysis as claimed in any one of claims 1 to 3, or the composite diaphragm for alkaline water electrolysis prepared by the preparation method as claimed in any one of claims 4 to 9 in hydrogen production by alkaline water electrolysis.

Citation Information

Patent Citations

  • Diaphragm for alkaline water electrolysis and preparation method and application thereof

    CN115029732A

  • Preparation method and application of composite alkaline polymer electrolyte membrane

    CN111864243A

  • Composite diaphragm for alkaline water electrolysis as well as preparation method and application of composite diaphragm

    CN116200779A

  • Composite diaphragm for alkaline electrolyzed water as well as preparation method and application of composite diaphragm

    CN117344346A

  • Alkaline water electrolysis composite diaphragm as well as preparation method and application thereof

    CN118186492A